Technology Transfer and Innovative Performance of The European Union’s Member States In 2018 - Marek PRONIEWSKI; Joanna Bogna ZIELINSKA (Communications of International Proceedings, 2021)
The aim of this paper is to evaluate the external factors’ input to the innovativeness of the European Union’s countries in 2018 and to compare it with their innovative performance. The authors have used the Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS) in order to rank Member States firstly on their ability to use technology transfer in the process of creation and diffusion of innovation, secondly - on the level of countries’ innovativeness. Further, the synthetic measures were compared with SII (summary innovation indices) in order to draw conclusions. As a result of the study, it was found that Ireland, Cyprus, Luxembourg, Sweden and Czech Republic have shown the greatest attractiveness for external technology transfer in 2018. Among them there are small economies with limited internal sources of innovativeness. Meanwhile the highest innovative performance in the EU was observed in Scandinavian and German-speaking countries: Germany, Ireland, Netherlands, Sweden, Austria and Finland. The Pearson correlation coefficient has confirmed a positive association on the moderate level between technology transfer and innovativeness among EU Member States in 2018.
Keywords: Innovativeness; technology transfer; European Union; TOPSIS.